Does Meeting Financial Expectations Boost Employee Satisfaction? - Hilary, Gilles; Tian, Xiaoli; Yu, Miaomiao (The Accounting Review, 2025)
ABSTRACT We investigate whether meeting Wall Street’s expectations affects rank-and-file employees’ satisfaction. Controlling for firms’ underlying financial performance, we find that those currently working for firms that meet or marginally beat analysts’ forecasts experience increased job satisfaction. This positive effect is concentrated among employees who are less transient, receive more nonexecutive stock options, or are more unionized. Furthermore, the positive effect exists only when employees do not incur higher costs associated with reaching the threshold because they overwork, suffer from labor law violations, or experience layoffs. Lastly, more senior or highly skilled employees respond more strongly when their employer meets Wall Street’s expectations. These results suggest that the effect of meeting earnings targets on employee satisfaction is significant when employees’ incentives align more with those of their employer or when employees are not unduly pressured. Data Availability: Data are commercially available. JEL Classifications: M41.